PERBEDAAN PERSEPSI ETIS MAHASISWA AKUNTANSI TERHADAP PRAKTIK MANAJEMEN LABA (STUDI PADA MAHASISWA AKUNTANSI PERGURUAN TINGGI SWASTA DI EKS-KARESIDENAN MADIUN) - Purbandari, Theresia (Widya Warta, 2012)
This study discusses the ethical perceptions of accounting students on the practice of earnings management. The purpose of this study is to prove that there are differences in ethical perceptions of accounting students on the practice of earnings management in terms of the type of earnings management, consistency of generally accepted accounting principles (GAAP), the direction of earnings management, materiality of earnings management, the period due to earnings management, and the objectives of earnings management.This study used primary data obtained directly from the answers of respondents through questionnaires. The data processing made use of data quality test, that is, validityand reliability testing. Normality test performed to determine the statistical tools that will be used to test the hypothesis. For normally distributed data the hypothesis 1-4 and 6, then used paired sample t test. For data not normally distributed the hypothesis 5, then used the Wilcoxon test. The results of hypothesis testing showed that hypotheses 1-4 are acceptable, while hypotheses 5-6 are not acceptable. This means that there are differences in ethical perceptions of accounting students on the variable of earnings management type, consistency with GAAP, the direction of earnings management, and materiality. Meanwhile, there is no difference in ethical perceptions of accounting students on variable of periods due to earnings management and the objectives of earnings management.